Patient understanding of disease and the use and outcome of implantable cardioverter defibrillators in hypertrophic cardiomyopathy. Issue 1 (28th December 2017) - Baskar, Shankar; Jefferies, John L.; Salberg, Lisa; Khoury, Philip R.; Spar, David S.; Knilans, Timothy K.; Czosek, Richard J.
Abstract: Hypertrophic cardiomyopathy (HCM) is the most common cause of sudden cardiac death (SCD) in young individuals. Implantable cardioverter defibrillators (ICD) are the primary therapy for sudden death prevention; however, are associated with both physical and psychological complications. We sought to determine factors associated with ICD understanding and patient satisfaction. This was a cross‐sectional study, using patient/parent answered questionnaires distributed to patients enrolled in the Hypertrophic Cardiomyopathy Association. Patient characteristics and satisfaction data were obtained via questionnaire. Patients were compared based on age at diagnosis and presence of ICD. ICD patients with high satisfaction were compared to those with low satisfaction to determine factors associated with poor satisfaction. A total of 538 responses were obtained (53 ± 16 years); 46% were females. Seventy patients (13%) were diagnosed with HCM < 18 years of age and 356 (66%) had an ICD. Compared to those without an ICD, patients with ICDs were younger at age of diagnosis (P = 0.001) and time of study (P = 0.008). Patients with ICDs were more likely to have presented with syncope and have family history of ICD, SCD, or HCM‐related death. Nineteen patients (5%) felt that issues surrounding their ICD outweighed its benefit. Compared to patients with a favorable satisfaction, the only significant difference was the preimplant ICD discussion (P < 0.001) and history of lead replacement (P = 0.01). In conclusion, the majority of HCM patients with ICDs are satisfied with their ICD management and feel the benefits of ICDs outweigh issues associated with ICDs. Additionally, these data highlight the importance of the preimplant patient‐physician discussion around the need for ICD prior to implantation.